FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SEKSUAL PRANIKAH PADA REMAJA PUTRI YANG TINGGAL DI KOST LINGKUNGAN V KELURAHAN PADANG BULAN KECEMATAN MEDAN BARU TAHUN 2013 - Juni Gultom; Ria Masniari Lubis; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Adolescents are those who are experiencing changes from childhood to adulthood. Psychologically adolescent tend to have a high curiosity and wanting to try new things. Issues of sexuality and reproductive health that is taboo to talk about, makes adolescents tend to want to experiment so teens be at risk on premarital sexual behavior. This research aims to know the factors associated with premarital sexual on young girls who live at the boarding house in Lingkungan V Kelurahan Padang Bulan Kecamatan Medan Baru in 2013. This research has been conducted with cross-sectional a analitic-descriptive. Sampling was done by a systematic random sampling with sample size is 86 young girls. Data were analyzed by chi square test with α 0.05. The results showed that premarital sexual relations conducted by 45 young girls (52,3%) who  having had sexual intercourse before marriage in boarding house,  from 45 young girls who living in the boarding house, it was found that 27 young girls (60,0%)  who did not live with owner boarding house. It was found that the factors associated significantly with premarital sexual are  knowledge (p<0.001), attitudes (p<0.001), resources information exposure (p<0.001), boarding house environment (p<0.001). From the results of the research are expected to headman of Lingkungan V Kelurahan Padang Bulan to improve monitoring, especially teenage don’t have owners live together  to make more explicit regulations, guests must report 1 x 24 hours to prevent the things that are not desired and to the owner who does not particularly boarding house supervised in order to provide a special room for guests.     Key words      : premarital sexual, boarding house, young girls